2010
DOI: 10.1302/0301-620x.92b7.22959
|View full text |Cite|
|
Sign up to set email alerts
|

A prospective, randomised trial comparing closed intramedullary nailing with percutaneous plating in the treatment of distal metaphyseal fractures of the tibia

Abstract: We compared the outcome of closed intramedullary nailing with minimally invasive plate osteosynthesis using a percutaneous locked compression plate in patients with a distal metaphyseal fracture in a prospective study. A total of 85 patients were randomised to operative stabilisation either by a closed intramedullary nail (44) or by minimally invasive osteosynthesis with a compression plate (41). Pre-operative variables included the patients' age and the side and pattern of the fracture. Peri-operative variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
163
1
17

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(199 citation statements)
references
References 22 publications
18
163
1
17
Order By: Relevance
“…Nonunion occurred in 8 % of the fractures in this study. This compares favourably to the reports by Im and Tae [6] and Vallier et al [32] nailing groups, whereby the rate of delayed and non-union after nailing distal tibial fractures vary between 0 and 23 % in the literature [3,6,8,13,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Screw failure remains a common problem with small diameter nails [2,15,16].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Nonunion occurred in 8 % of the fractures in this study. This compares favourably to the reports by Im and Tae [6] and Vallier et al [32] nailing groups, whereby the rate of delayed and non-union after nailing distal tibial fractures vary between 0 and 23 % in the literature [3,6,8,13,14,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Screw failure remains a common problem with small diameter nails [2,15,16].…”
Section: Discussionsupporting
confidence: 73%
“…This may support early dynamisation in axially stable fractures to avoid delayed union and fatigue failure of the locking screws. Multiple prospective [6,[32][33][34] and retrospective [7,8,31] studies comparing open plating and locked intramedullary nailing for distal tibial fractures have described similar results as regards infection, secondary procedures, time to union (17-27 weeks) and rate of non-union (0-9 %) for both techniques. Whereas nailing has the advantage of shorter operative duration and reduced wound problems, ORIF can restore alignment better than nailing that was associated with more malunion (Table 2).…”
Section: Discussionmentioning
confidence: 96%
“…Li et al [1] have reported no delayed union or nonunion in their retrospective study involving twenty-threepatients treated with MIPO. Guo et al [16] reported no delayed union or nonunion in their prospective randomised study involving forty-one patients treated with MIPO. Seyhan et al [5] have reported two (5.6%) nonunion with MIPO in their retrospective study.…”
Section: Discussionmentioning
confidence: 97%
“…Successful radiological and clinical outcomes were recommended with this technique. [15][16][17] Traditional open surgical technique is based on absolute stability achieved by full contact at the fracture side, and rigid internal fixation; however, open surgery has some limitations, such as infection, and long hospital stay. [5] Delayed union, and nonunions are important morbidities in the treatment of distal tibia fractures and common findings.…”
Section: Discussionmentioning
confidence: 99%
“…IMN, which is a minimally invasive and biological method, provides symmetrical and dynamic fracture fixation (3,4). However, for fractures very close to the joint, the distal type of nail and the locking mechanism cannot provide adequate stability, especially when the distal fragment is very short.…”
Section: Introductionmentioning
confidence: 99%